ZIYARAT TOURISM" IN THE MARKET OF INTERNATIONAL SERVICES THE ROLE AND IMPORTANCE OF INTEGRATED MARKETING METHODS IN BRAND FORMATION AND EFFICIENCY IMPROVEMENT - Anvar Aidjanovich Khudoyarov (Journals Park Publishing, 2024)
In scientific work Developing relations of Uzbekistan with international organizations and foreign countries in the field of tourism, increasing the flow of tourists to our country, creating all conditions for providing services to tourists, improving the quality and culture of service, training personnel in the field organizational and economic that regulates relations related to aspects have been considered.
Keywords: Pilgrimage tourism, diversification, brand, safety, legal-economic base, standard, tolerance, marketing.